2022
DOI: 10.1002/lio2.893
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on presentation and diagnosis of head and neck squamous cell carcinoma

Abstract: Objective To analyze how the COVID‐19 pandemic has influenced trends in head and neck squamous cell carcinoma (HNSCC) presentation and diagnosis—including referral patterns, stage at presentation, and time to diagnosis—over a longitudinal time course. Setting Multicenter tertiary care academic institution. Methods A retrospective review of patients with HNSCC presenting between January 1, 2019 and December 31, 2020 was performed. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[19] Different from these results, other studies that evaluated the impact of the COVID-19 pandemic on the diagnosis of new cases of HNSCC demonstrated a reduction from 22% to more than 50% of new diagnoses during the pandemic, but the stage of the disease and the time of diagnosis were similar in the groups before and during the pandemic. [9,20] This suggests that, in our study, although the number of patients who received the diagnosis in both groups was similar, in the COVID-19 group, patients must have taken longer to seek care after the onset of the rst signs and/or symptoms, which may have impacted on the delay in diagnosis, and, consequently, the cases, when they were diagnosed, already had greater lymph node involvement.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…[19] Different from these results, other studies that evaluated the impact of the COVID-19 pandemic on the diagnosis of new cases of HNSCC demonstrated a reduction from 22% to more than 50% of new diagnoses during the pandemic, but the stage of the disease and the time of diagnosis were similar in the groups before and during the pandemic. [9,20] This suggests that, in our study, although the number of patients who received the diagnosis in both groups was similar, in the COVID-19 group, patients must have taken longer to seek care after the onset of the rst signs and/or symptoms, which may have impacted on the delay in diagnosis, and, consequently, the cases, when they were diagnosed, already had greater lymph node involvement.…”
Section: Resultsmentioning
confidence: 59%
“…[6][7][8] The restrictions imposed by the COVID-19 pandemic also had an impact on reducing the number of new diagnoses of head and neck cancer. [9,10] With the social distancing measures adopted to control the spread of the COVID-19 pandemic in Brazil, it is believed that, as in other countries, many patients stopped seeking care to evaluate head and neck injuries, resulting in a delay in the diagnosis and, consequently, a worse prognosis for the patient. [11] There is little evidence on the impact of COVID-19 on the diagnosis and extent of head and neck cancer in low-income countries, especially considering confounding variables.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic affected both the diagnosis and treatment of many cancer sites, including HNC . Several studies have reported disparities associated with access to care during the COVID-19 pandemic, which may have affected stage at presentation and survival outcomes of patients with cancer, especially among individuals with limited access to care .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The COVID-19 pandemic affected both the diagnosis and treatment of many cancer sites, including HNC . [7][8][9] Several studies have reported disparities associated with access to care dur-ing the COVID-19 pandemic, which may have affected stage at presentation and survival outcomes of patients with cancer, especially among individuals with limited access to care. [10][11][12] However, although studies have described the epidemiology and outcomes of HNC associated with the COVID-19 pandemic, the generalizability of these studies to the HNC population in the US has been limited, as most have been either from a single institution, aggregated data from multiple institutions, or studies with data outside of the US.…”
mentioning
confidence: 99%
See 1 more Smart Citation